A Single Hydrogen Bond Controls the Selectivity of Transglycosylation vs Hydrolysis in Family 13 Glycoside Hydrolases - Guo, Zhiyong; Wang, Lei; Su, Lingqia; Chen, Sheng; Xia, Wei; André, Isabelle; Rovira, Carme; Wang, Binju; Wu, Jing (The journal of physical chemistry letters, 2022)
Converting glycoside hydrolases (GHs) from hydrolytic to synthetic enzymes via transglycosylation is a long-standing goal for the biosynthesis of complex carbohydrates. However, the molecular determinants for the selectivity of transglycosylation (T) vs hydrolysis (H) are still not fully unraveled. Herein, we show experimentally that mutation of one active site residue can switch the enzyme activity between hydrolysis and transglycosylation in two highly homologous GHs. Further QM/MM simulations reveal that the mutation modulates the T vs H reaction barriers via the presence/absence of a single H-bond with the nucleophile Asp. Such a H-bond controls the product selectivity via a dual effect: on one hand, it facilitates the breaking of the glycosyl-enzyme intermediate. On the other, it displaces the sugar acceptor, resulting in a reduced affinity and significant steric repulsion for transglycosylation. These findings expand our understanding of the molecular mechanisms that modulate the T/H balance in GHs.